Localization of the Serotonin Transporter in the Dog Intestine and Comparison to the Rat and Human Intestines - Chiocchetti, Roberto; Galiazzo, Giorgia; Giancola, Fiorella; Tagliavia, Claudio; Bernardini, Chiara; Forni, Monica; Pietra, Marco (Frontiers in Veterinary Science, 2022)
Serotonin is crucial in gastrointestinal functions, including motility, sensitivity, secretion, and the inflammatory response. The serotonin transporter (SERT), responsible for serotonin reuptake and signaling termination, plays a prominent role in gastrointestinal physiology, representing a promising therapeutic target in digestive disorders. Serotonin transporter expression has been poorly investigated in veterinary medicine, under both healthy and pathological conditions, including canine chronic enteropathy, in which the serotonin metabolism seems to be altered. The aim of the present study was to determine the distribution of SERT immunoreactivity (SERT-IR) in the dog intestine and to compare the findings with those obtained in the rat and human intestines. Serotonin transporter-IR was observed in canine enterocytes, enteric neurons, lamina propria cells, and the tunica muscularis. Data obtained in dogs were consistent with those obtained in rats and humans. Since the majority of the serotonin produced by body is synthesized in the gastrointestinal tract, SERT-expressing cells may exert a role in the mechanism of serotonin reuptake.